Thermomagnetic Analysis of the Lake Matano Sediments and the Surrounding Lateritic Soils, South Sulawesi, Indonesia - Silvia Jannatul Fajar; Gerald Tamuntuan; Satria Bijaksana; James Russell (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
Thermomagnetic is one of the most commonly used measurements for determining the dominant type of magnetic mineral of samples. The measurement is separated into two distinct processes, heating and cooling. The sample susceptibility is measured for each temperature change, i.e., from room temperature to 700oC and vice-versa. Based on the thermomagnetic measurement results, magnetite is found to be the predominant magnetic minerals in Lake Matano sediments. The present study applied a correlation analysis technique on the results of thermomagnetic measurement of Lake Matano sediments and compared the result to that of lateritic soils to indicate whether a diagenetic process has occurred on the lake sediments.